Elephant Trails : A History of Animals and Cultures - Rothfels, Nigel (Book collections on Project MUSE., 2021)
"The author traces a group of ideas about elephants in the West-that they are wise, deeply emotional, have a special understanding of death, have great memories, and are afraid of mice-to paint a general picture of what he calls "our elephant," the idea of the elephant that has been part of our thinking for millennia. The book is an intellectual and cultural history of the elephant that uses a broad range of published sources along with traditional and less usual archives"--